2000
DOI: 10.1136/sti.76.5.345
|View full text |Cite
|
Sign up to set email alerts
|

Sexually transmitted infections and risk behaviours in women who have sex with women

Abstract: Objectives:To assess the prevalence of sexually transmitted infections (STIs) and blood borne viruses, risk behaviours, and demographics in women who have sex with women (WSW). Methods: Retrospective cross sectional study using a multivariate model. Demographic, behavioural, and morbidity data were analysed from standardised medical records of patients attending a public STI and HIV service in Sydney between March 1991 and December 1998. All women with any history of sex with a woman were compared with women w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

12
125
1
12

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 225 publications
(150 citation statements)
references
References 19 publications
12
125
1
12
Order By: Relevance
“…However, it is increasingly appreciated that these women may be at risk through their ongoing sexual behaviors with men (Fethers, Marks, Mindel, & Estcourt, 2000;Goodenow et al, 2008). Infections that occur through those encounters are counted as "heterosexual" transmissions in surveillance data, making it difficult to know the disease burden among women who identify as lesbian or bisexual.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is increasingly appreciated that these women may be at risk through their ongoing sexual behaviors with men (Fethers, Marks, Mindel, & Estcourt, 2000;Goodenow et al, 2008). Infections that occur through those encounters are counted as "heterosexual" transmissions in surveillance data, making it difficult to know the disease burden among women who identify as lesbian or bisexual.…”
Section: Introductionmentioning
confidence: 99%
“…Additional findings have demonstrated that bacterial vaginosis was significantly more common in WSW than in women who denied ever having had sex with women. 15 Studies have also shown that human papillomavirus (HPV) transmission can occur between female sex partners. [16][17][18] Forced sex with men has also been identified as a risk factor for self-reported HIV infection among WSW in southern Africa.…”
mentioning
confidence: 99%
“…Seks oyuncaklarının ortak kullanımı gibi oral-vajinal ve dijital-vajinal davranışlar mevcut enfekte olan servikovajinal salgıların geçişini kolaylaştıra-bilir ve trikomonas, HIV ve diğer CYBE riskini artırabilir. 17,19,20 Genital herpes veya genital siğil öyküsü, biseksüellerde (%15,0-17,2) lezbiyenlere (%2,3-6,7) göre daha sık bildirilmiştir. 16 2001-2006 yılları arasında, 18-59 yaş grubu kadınlarla yapılan bir çalış-mada, son bir yıl içinde aynı cinsiyetten partnere sahip olan kadınlarda HSV-2 seroprevalansı %30,3, yaşamları boyunca aynı cinsiyetten partnere sahip olan kadınlarda %36,2 ve yaşamları boyunca aynı cinsiyetten partnerle cinsel davranışlar içine girmeyen kadınlarda %23,8 olarak saptanmıştır.…”
Section: Sağlik Ri̇skleri̇unclassified
“…22,23 Çalışmalar, lezbiyenlerde BV prevalansının da yüksek (%8-52) olduğunu göstermektedir. 19,20,24 Büyük örneklemli bir çalışmada, lezbiyenlerde BV (%45,2) prevalansı heteroseksüel gruba (%28,8) göre daha yüksek bulunmuştur. 25 Kadın cinsel partner ve BV arasındaki ilişkiyi inceleyen sistematik çalışma ve meta-analiz sonuçları, kadın seks partnerine sahip olan kadınlarda BV gelişme riskinin iki kat fazla olduğunu göstermektedir.…”
Section: Sağlik Ri̇skleri̇unclassified